2017
DOI: 10.4236/ojpm.2017.72002
|View full text |Cite
|
Sign up to set email alerts
|

Taichi Softball as a Novel Chinese Health-Promoting Exercise for Physical Health: A Systematic Review and Meta-Analysis

Abstract: Background: Taichi softball was voted as one of the most popular healthpromoting exercises in the category of ball games, which is attributed to that Taichi softball is not only beneficial for lower extremity-related physical health (e.g., balance, leg strength, and flexibility), but can also develop manipulative skill and hand-eye coordination (eating, bathing, dressing, bathing required manipulative skills, grips movement and strength). However, the positive effects of Taichi softball on physical health have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
2
2
0
1
Order By: Relevance
“…Participants from both groups were recruited from a senior living center; previous studies had shown that, without exercise, motor functions of older people would experience an age-related normal decline, which corresponds to our findings [34, 61]. For timing tests such as Moberg Pickup Test and Time Up and Go Test, we see a significant decrease in fine motor perception as well as a decrease in whole body movement speed.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Participants from both groups were recruited from a senior living center; previous studies had shown that, without exercise, motor functions of older people would experience an age-related normal decline, which corresponds to our findings [34, 61]. For timing tests such as Moberg Pickup Test and Time Up and Go Test, we see a significant decrease in fine motor perception as well as a decrease in whole body movement speed.…”
Section: Discussionsupporting
confidence: 86%
“…As we know the control group maintained their normal lifestyles during the intervention period; however, within-group analysis showed that the control group had significant differences in assessment tests such as Spiral Drawing Test, Moberg Pickup Test, Arm Curl-Up Test, Back Scratch Test, Chair Stand Test, and Time Up and Go Test between baseline and after 7 weeks ( Table 2 ). Participants from both groups were recruited from a senior living center; previous studies had shown that, without exercise, motor functions of older people would experience an age-related normal decline, which corresponds to our findings [ 34 , 61 ]. For timing tests such as Moberg Pickup Test and Time Up and Go Test, we see a significant decrease in fine motor perception as well as a decrease in whole body movement speed.…”
Section: Discussionsupporting
confidence: 84%
“…Качество жизни у лиц с ожирением несравнимо хуже, чем у лиц с нормальной массой тела [9]. По данным исследований и метаанализов, избыточная масса тела и ожирение непосредственно связаны с высокой частотой сопутствующих заболеваний [10][11][12]. Статистически значимые ассоциации выявлены между ожирением и СД 2-го типа, всеми видами рака (кроме рака пищевода и предстательной железы), ССЗ, астмой, заболеваниями желчного пузыря и опорно-двигательного аппарата [11,13].…”
unclassified
“…The softball racquet consists of a soft rubber rubber soft-faced frame and a handle made of lightweight material. The Tai Chi Softball [8] is a rubber ball weighing 53-55 grams and having no elasticity and 7 cm in diameter. Taichi Softball Division is divided into singles and doubles.…”
Section: Introductionmentioning
confidence: 99%